Death from Liver Failure despite Lamivudine Prophylaxis during R-CHOP Chemotherapy due to Rapid Emergence M204 Mutations - Lay Lay Win; Jeff Powis; Hemant Shah; Jordan J. Feld; David K. Wong (Case Reports in Hepatology)
Background. Rapid and early emergence of clinically significant LAM resistance is thought to be unlikely during the first year of treatment, and as a result LAM is thought to be a reasonable choice as a first line agent for prophylaxis during chemotherapy. Aim. To report fatal HBV reactivation despite appropriate LAM prophylaxis in two previously treatment-naive individuals undergoing R-CHOP chemotherapy. Case Presentation. Case 1 is a 65-year-old man with chronic HBV infection: HBeAg-negative, HBV DNA 6.65E5 IU/mL, ALT 43 IU/L, and Fibroscan 4.4 kPa, consistent with F0, who was diagnosed with lymphoma that was treated with R-CHOP and LAM prophylaxis. HBV DNA fell to 2.18E1 IU/mL within 2 months of starting LAM. Four months after chemotherapy, despite ongoing LAM of 7-month duration with confirmed adherence, severe asymptomatic hepatitis was noted during routine monitoring with ALT 1019 IU/L, HBeAg negative, HBV DNA 1.43E7 IU/mL, and genotyping confirmed L80I and M204I mutations. He died 14 days after flare diagnosis despite a switch to tenofovir (HBV DNA had fallen to 1.94E5 IU/mL 2 weeks after starting tenofovir). Case 2 is a 50-year-old man who was found to have HBeAg-negative hepatitis B, ALT 37 IU/L, and no clinical features of cirrhosis (platelets 283, APRI 0.19) after lymphoma diagnosis. Lymphoma was treated with R-CHOP and LAM prophylaxis. Pretreatment HBV DNA was not done but was 8.90E4 IU/mL 3 weeks after starting LAM and 3.96E3 IU/mL 3 months after starting LAM. Two months after chemotherapy, despite ongoing LAM of 7-month duration with confirmed adherence, severe symptomatic hepatitis presenting with jaundice, abdominal pain, and confusion was noted. ALT 902 IU/L, HBeAg negative, HBV DNA 1.02E8 IU/mL, and genotyping confirmed L80I, M80V, and M204V/S mutations. He died 3 days after flare diagnosis despite the addition of tenofovir. Conclusion. Lamivudine should not be used for prophylaxis of patients with chronic hepatitis B with detectable HBV DNA undergoing chemotherapy with rituximab containing cytotoxic chemotherapy even if they have never had exposure to lamivudine in the past. In this setting, lamivudine failure due to resistance can develop quickly leading to liver failure that cannot be salvaged with tenofovir. Whether LAM is safe for prophylaxis with rituximab-based cytotoxic chemotherapy for patients with undetectable HBV DNA is unknown, but agents with a high barrier to resistance may be preferable.